Pengaruh Sinar UV-C terhadap Perubahan Mutu Wortel (Daucus carota L.) Selama Penyimpanan - Nesti Kurnia Ningsih; Dwi Dian Novita; Tamrin Tamrin (abe.fp.unila.ac.id, 2023)
Based on the survey result of vegetable crop production in Indonesia, the national carrot harvest area is 13,398 hectares spread over 16 provinces. Meanwhile, the average carrot production in Lampung Province can reach 16,02 tons/year with a harvested area of 369 hectares (BPS, 2018). Damage to horticultura commodities can occur if the post-harvest handling is not done well. Many problems were found related to the decay of agricultural products due to the development of microorganisms which caused gread losses for farmers. Sterilization with UV lamps is an attempt to kill and eliminate pathogens or spoilage microbes that cause food spoilage. This sterilization aims to determine the effect of UV-C rays on the quality of carrot during storage. This research was conducted using a completely randomized design (CRD) with 2 factors, namely the irradiation distance factor (20 cm, 40 cm, and 60 cm) and the irradiation time (1-, 20, and 30 minutes). The data obtained were analyzed by ANOVA test. In the 60 cm irradiation distance treatment with an irradiation time of 30 minutes is the recommended storage distance because it can suppress root growth with an average value of 16,67 %, physical damage 14,58%, and gives the panelists the best assessment of the freshness level parameter with an average value of 3,24 (scale 5), texture with an average value of 3,25 (scale 5), and skin appearance with an average value of 3,15 (scale 5). Keywords: Carrots, Microbes, Influence, UV-C Rays, Radiation